PENGARUH VARIABEL KARAKTERISTIK INDIVIDU, MOTIVASI KERJA DAN SISTEM IMBALAN TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN SUPERMARKET DI KOTA GORONTALO - Rosmina Hiola (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
The research objective to be achieved is to determine the characteristics of the individual, motivation and reward system on the performance of employees at six supermarket companies in the city of Gorontalo. The sample was 342 out of a population of all employees, amounting to 2367 people. Data collection techniques, interviews were conducted using a model questionnaire and observation techniques. To examine the relationship models used analysis tool capable of simultaneously explaining the relationship is by using path analysis. Results of this study suggests that individual characteristic variable (X1) partially affect the performance of employees is 0.619, or approximately 61.9% and the effect of work motivation (X2) partially affect the performance of employees is 0.704, or approximately 70.4%, system variables in return for partial influence on the performance of employees is 0.724, or approximately 72.4%. collectively contribute - together (simultaneously) variables individual characteristics, (X1) and motivation (X2) and a system of rewards (X3) on employee performance (Y) by 76% and the remaining 24% is determined by variables - variables not examined , the work environment, organizational characteristics.